ATTITUDE OF SMALL-SCALE FARMERS TOWARDS THE USE OF DIGITAL APPLICATIONS FOR PARTICIPATORY MONITORING - Agnese, Federica; Othman, Zakirah (CENTRAL ASIA AND THE CAUCASUS, 2021)
Digital applications for participatory monitoring in management are increasingly used for knowledge sharing and collective actions in agriculture. Therefore, this study aims to assess the attitude of small-scale farmers towards the use of digital applications for participatory monitoring. The theory of planned behavior has been utilized as theoretical framework. A qualitative case study research of the project of System of Rice Intensification Farmer Field School in West Malaysia was carried out. The research was conducted in relation to the digital applications of WhatsApp, Google Forms and online interview. In this study, the sampling was purposive and included small-scale farmers and farmer trainers in three locations. After the collection of data from October 2020 to March 2021, the interviews and the project’s milestone reports were analyzed through thematic and content analyses. The findings showed that the indicators of commitment, trust, resources, time and recognition have positive influence towards the use of digital applications for participatory monitoring. The study concluded that these indicators must be included in the design of digital applications protocols, particularly the integration of traditional practices and cultural values were found determinants for the small-scale farmers and farmer trainers attitude towards the use of digital applications for participatory monitoring. This study recommends further research on the relationship of small-scale farmers place attachment and participatory monitoring.